Eficiência produtiva e pobreza rural no Nordeste brasileiro - Felipe Pinto da Silva; Jair Andrade Araujo; Edward Martins Costa; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This study aims to analyze the technological differences in agricultural production between the municipalities in the semiarid and non-semiarid regions of Brazil's Northeast. It uses the technological meta-frontier model proposed by Battese, Rao e O'Donnell (2004), and O'Donnell, Rao e Battese (2008), for responding to what extent these regional differences influence the efficiency of production and what is its impact on municipalities. It was observed the hypothesis that municipalities belonging to the semiarid and non-semiarid have different production opportunities. The results indicated that when compared the two regions, the non-semiarid region has the highest average technical efficiency with reference to meta-frontier.
Keywords: D24; Q10; 330; agriculture; technology; semi-arid northeast; production meta-frontier